Waktu Pemberian Analgesik dengan Kepuasan Pasien yang Mengalami Nyeri Akut di Instalasi Gawat Darurat - Ode Irman (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Acute pain is one of the main complaints that is often the reason for patients to come to the Emergency Installation (IGD) and is an important indicator in assessing the quality of nursing care. Fast and appropriate pain management will increase patient comfort and satisfaction with health services. One of the factors that greatly affects the reduction in pain is the timing of the administration of analgesics. The sooner the analgesic is administered, the more effective it is at reducing pain, which ultimately impacts the patient's satisfaction level. This study aims to explain the relationship between the time of analgesic administration and the satisfaction level of patients who experience acute pain in the emergency room. The type of research used is correlation analytics with cross-sectional designs. The sampling technique used accidental sampling with a total of 43 respondents, according to the inclusion criteria. The research was conducted in May 2025. Data on the timing of analgesic administration were collected through observation sheets, while patient satisfaction data was obtained using a structured questionnaire. The results showed that most of the patients who received analgesics did not match the recommended time felt dissatisfied, namely 26 people (60.5%). Based on the results of the contingency coefficient test, a value of p = 0.000 was obtained, which means that H0 was rejected and Ha was accepted. This shows a significant relationship between the speed of analgesic administration and patient satisfaction. The sooner the analgesic is administered after a pain assessment, the higher the patient's level of satisfaction with the services provided. Therefore, emergency room nurses are expected to increase responsiveness in administering analgesics, starting from assessment, determination of interventions, to implementation according to hospital standard operating procedures (SPO).